Clinical Characteristics of Bowel Obstruction in Southern Iran; Results of a Single Center Experience - Majid Akrami; Ali Ghaeini Hesarooeih; Maryam Barfei; Vahid Zangouri; Zahra Alborzi (Bulletin of Emergency and Trauma, 2015)
Objective: To determine the epidemiological, clinical, laboratory characteristics as well as outcome of 411 patients with bowel obstruction in Southern Iran. Methods: This was a cross-sectional study being performed in Shahid Faghihi hospital of Shiraz between 2006 and 2012. We reviewed the medical charts of the 411 patients with initial diagnosis of bowel obstruction who were admitted to our center during the study period. The patients’ demographic, clinical and laboratory findings as well as their management and outcome was recorded in data gathering forms. The data were then analyzed according to the outcome and clinical characteristics. Results: Among the 411 patients with initial diagnosis of bowel obstruction, 253 (61.5%) were men and 158 (38.5%) were women. The mean age of the patients was 48.2±19.7 years. Besides, 73.6% were observed and 26.4% were operated. Those who were operated had those who underwent operation had significantly lower frequency of obstipation (28.1% vs. 71.9%; p=0.045) and abdominal distention (32.3% vs. 67.7%; p=0.007). Intraoperative findings included adhesion band formation in 50 (48.1%), mass 18 (17.3%), and hernia 7 (6.7%). We found that the frequency of malignancy was significantly higher in those who were managed conservatively compared to those undergoing operation (64.3% vs. 35.7%; p=0.042). The mean hospital stay was significantly higher in those who underwent operation (8.1 ±7.5 vs. 2.6±2.2 days; p=0.035).Conclusion: The results of this study demonstrates although some signs and symptoms, such as abdominal pain, vomiting, abdominal tenderness, abdominal distention, and obstipation, were more common among the patients with bowel obstruction, they were not sensitive and specific enough for definite diagnosis. Due to the lack of positive predictive value of clinical signs and symptoms in diagnosis of bowel obstruction, a reasonable and logical modality is needed for bowel obstruction diagnosis with better accuracy.